ANALISIS SEKTOR UNGGULAN DAN PERUBAHAN STRUKTUR EKONOMI DI KABUPATEN/KOTA PROVINSI BANTEN - Farida, Syarifah Ida (RJABM (Research Journal of Accounting and Business Management), 2020)
The purpose of this study was to determine the leading sectors and changes in economic structure in the Regency / City of Banten Province. The research method used is the Location Quotient (LQ) analysis and Shift Share analysis. The data in this study use secondary data in the form of the value of the Gross Regional Domestic Product (GRDP) of Banten Province obtained from the Central Statistics Agency. The results based on the Location Quotient Analysis show that the service sector still dominates in economic growth in the Regency / City of Banten Province, followed by the agriculture and construction sectors. While the results of the Shift Share analysis show regional growth, mix of compositions and competitive advantages as well as the highest economic growth found in the city of Tangerang.